Wind Instruments: Wood - Jane Beethoven; Rosanne Emery; Cliff Lenz.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1991)
Viewers see and hear woodwind instruments from different parts of the world - - Discover the different ways in which sound is produced on woodwind instruments - - Take a look at familiar instruments, such as the flute, oboe, and bassoon, as well as unfamiliar instruments, such as the sao flute from Vietnam and the panpipes from South America - - Explore different styles of music, from baroque to folk to jazz.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - For Discussion - - For Students to Discover - - Student Follow-up - - Correlations with THE MUSIC CONNECTION - - Vocabulary - Music Contents - - About the Library.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: Woodwind instruments; Musical instruments; Films for the hearing impaired